MAIN CHARACTERISTICS OF THE BASHKIRIAN STAGE CARBONATE SEDIMENTS (ILLUSTRATED BY THE EXAMPLE OF VELYKOBUBNIVS’KA FIELD OF THE DNIPRO-DONETS DEPRESSION) - Tkachenko, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Carbonate reservoirs are the main sites in production of hydrocarbons in the world, while in Ukraine these collectors are insufficiently studied and only now these sediments start to be studied. Carbonate reservoirs in the Dnipro-Donets depression are presented in the Bashkirian stage (Bashkirian "plate") and Lower Visean sediments (Lower Visean "plate"). For the first time ever, close attention is paid to the main characteristics of carbonate sediments of the Bashkirian stage on Velykobubnivs’ka field of the Dnipro-Donets depression. The geological and petrophysical characteristics, features of carbonate reservoir rocks are exemplified by the wells 119 and 139. The Bashkirian rocks are represented by algal slime limestones, with hidden crystal structure with disseminated pyrite and greenish-gray argillites, layers of siltstone, limestone and light gray sandstone, quartz. Thicknesses of horizon B-9n on the territory of Velikobubnivs`ka field are presented on the map. Thickness of carbonate deposits were estimated on the basis of the map. In particular, they reach 6 m in the northwest and 5 m thick and are distributed almost uniformly over the entire area. The increase the absolute depth of the top horizon of B-10 from north to south is shown on the structural map. According to complex logging methods, carbonate formations with bed thickness from 6 to 8 m (horizon B-9) and from 6 to 13 m (horizon B-10) were allocated, which can be characterized as reservoir rocks. Porosity of Bashkirian carbonate deposits (Horizons B-9, B-10) in the Dnipro-Donets depression is changed in a wide range from 5 to 22%, while the average values, generally, do not exceed 3-5%. The characteristic feature of productive layers comprising bashkirian carbonate rocks, is high anisotropy of filtration and capacitive properties even within the same area. In accordance with logging data interpretation and results of industrial tests, Bashkirian deposits on the Velikobubnivs`ka field can be determined as perspective to search for gas and oil.